SEMANTIC DEVELOPMENT IN ARABIC LANGUAGE (AN ANALYTICAL STUDY ON DIWAN ABI TAMMAM) / Ø§Ù„ØªØ·ÙˆØ± Ø§Ù„Ø¯Ù„Ø§Ù„ÙŠ ÙÙ‰ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© (Ø¯Ø±Ø§Ø³Ø© ØªØÙ„ÙŠÙ„ÙŠØ© Ø¹Ù† Ø¯ÙŠÙˆØ§Ù† Ø£Ø¨ÙŠ ØªÙ…Ø§Ù…) - Rita Zahara (IAIN Batusangkar, Indonesia, 2021)
This study aims to determine the development of Arabic semantics in Diwan Abi Tammam book. Abu Tammam is a modern Arabic poet. He has poetry books which have been printed several times and all of his poetry is collected in a book that is known as Diwan Abi Tammam. This research is limited to the types of semantic development. The method used was content analysis. This study begins with an analysis of semantic development in Arabic and then its application in the Diwan Abi Tammam book. The results of this study indicate that the types of semantic development in Diwan Abi Tammam are grammatical and phonemic semantics. The grammatical semantic elements include the meaning of a sentence based on the elements of imagination, aesthetics, stylistic and rhetoric. Whereas, the semantic phonemic elements include the meaning of characteristics of several composed sounds and these sounds have a meaning role in a word such as the differences in the use of halqi, ra’, and sin, and their influence on the meaning of the target object.